Application of TPI1-10k/50 thyratrons for building a modulator, intended for supply of inductive-resistive load in double-pulse mode - Akimov, A.V.; Logachev, P.V.; Bochkov, V.D.; Bochkov, D.V.; Dyagilev, V.M.; Ushich, V.G. (Вопросы атомной науки и техники, 2008)
The circuit of modulator, serving to supply inductive-resistive load in double-pulse mode with currents up t10 kA and pulse duration of 300 ns, is described. As switching components TPI1-10k/50 thyratrons (pseudospark switches) with anode voltage up to 50 kV have been used. The results of tests, confirming possibility of the thyratron reverse dielectric strength recovery within some microseconds after switching of 10 kA forward anode current, are presented. Описано схему модулятора, що забезпечує живлення індуктивно-резистивного навантаження у двох-імпульсному режимі з імпульсними струмами до 10 кА і тривалістю імпульсу 300 нс. У якості коммутаторов використані тиратрони (pseudospark swіtches - PSS) ТПИ1-10k/50 з анодною напругою до 50 кВ. Представлено результати випробувань, що підтверджують можливість відновлення зворотної электрической міцності тиратрону за одиниці мікросекунд після протікання прямого анодного струму до 10 кА. Описана схема модулятора обеспечивающего питание индуктивно-резистивной нагрузки в двух-импульсном режиме с импульсными токами до 10 кА и длительностью импульса 300 нс. В качестве коммутаторов использованы тиратроны (pseudospark switches - PSS) ТПИ1-10k/50 с анодным напряжением до 50 кВ. Представлены результаты испытаний, подтверждающие возможность восстановления обратной электрической прочности тиратрона за единицы микросекунд после протекания прямого анодного тока до 10 кА.